Effect of advanced and injectable platelet-rich fibrins against Aggregatibacter actinomycetemcomitans in subjects with or without periodontal diseases - Phuong Tran, Thao Thi; Vu Pham, Thuy Anh (Journal of dental sciences, 2023)
Background/purpose: Data for comparing effects of advanced platelet-rich fibrin (A-PRF+) and injectable platelet-rich fibrin (i-PRF) against Aggregatibacter actinomycetemcomitans (Aa) in subjects with differently periodontal conditions are scarce. This study aimed to compare the antimicrobial capacity of A-PRF+ and i-PRF obtained from subjects with or without periodontal diseases against the pathogenic bacteria Aa. The number of red blood cells, platelets, and white blood cells on the blood samples of 60 individuals, including healthy subjects (n = 20), patients with gingivitis (n = 20), and patients with periodontitis (n = 20), were analyzed before preparing A-PRF+ and i-PRF. In addition, the in vitro antibacterial effect of the two platelet concentrates was evaluated by using the agar diffusion test and a minimum inhibitory concentration (MIC) experiment. I-PRF exhibited a significantly better antibacterial effect than A-PRF+ within the gingivitis and periodontitis groups, with a more expansive zone of inhibition and a lower MIC. Among the studied groups, the A-PRF+ and i-PRF collected from the periodontitis group inhibited Aa significantly more compared with the gingivitis and healthy groups. Although both A-PRF+ and i-PRF exhibited an antibacterial effect against Aa through the zone of inhibition and MIC tests, in the gingivitis and periodontitis groups, i-PRF exhibited better antibacterial activity than A-PRF+, and PRF products from the periodontitis group had greater effects against Aa than PRF products from the two other groups.